2017
DOI: 10.1155/2017/3616875
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Oral Dydrogesterone and Vaginal Progesterone on Threatened Abortion: A Systematic Review and Meta-Analysis

Abstract: Objective To conduct systematic analyses to evaluate the efficacy of progesterone therapy for the prevention of miscarriages in pregnant women experiencing threatened abortion. Methods In November 2016, we performed a systematic literature search and identified 51 articles in PubMed, Embase, and Cochrane databases. We identified nine randomized trials that included 913 pregnant women (including 322 treated with oral dydrogesterone, 213 treated with vaginal progesterone, and 378 control subjects) who met the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 27 publications
(30 reference statements)
1
39
0
3
Order By: Relevance
“…This can be one of the mechanisms of the various beneficial effects of dydrogesterone. Moreover, the results of a systematic review and a randomized controlled trial indicated that the oral dydrogesterone therapy can effectively prevent threatened miscarriage in pregnant women …”
Section: Discussionmentioning
confidence: 99%
“…This can be one of the mechanisms of the various beneficial effects of dydrogesterone. Moreover, the results of a systematic review and a randomized controlled trial indicated that the oral dydrogesterone therapy can effectively prevent threatened miscarriage in pregnant women …”
Section: Discussionmentioning
confidence: 99%
“…(2017) in their mata-analysis stated that the incidence of abortion was significantly reduced in the progesterone group than in the control group (13.0% versus 21.7%) [14]. On the other hand, Duan et al (2010) in their study compared intramuscular progesterone to no treatment in threatened abortion.…”
Section: Discussionmentioning
confidence: 97%
“…Previous meta-analyses did not assess the effect of progestogen on live birth. 12,13 In those reviews, miscarriage was the primary outcome. Lee et al found that progestogen therapy can effectively reduce miscarriage events in pregnant women experiencing threatened miscarriage (RR 0.53, 95% CI 0.36-0.78).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Previous systematic reviews and meta-analyses suggested that progestogen may reduce the risk of miscarriage in pregnant women with threatened miscarriage. 12,13 However, these reviews only included small trials with several hundred women and were thus limited in statistical power. Moreover, these reviews did not assess the rate of live birth, which is the most important clinical outcome for pregnancy.…”
Section: Introductionmentioning
confidence: 99%